The contribution of agriculture to sustainable development in Jamaica - Arias Segura, Joaquín (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
This paper shows that the contribution of agriculture to GDP is, in fact, underreported. It outlines an alternative approach to assessing the sector’s performance and introduces the concept of expanded agriculture, which seeks to highlight agriculture’s linkages with the wider economy. This expanded concept of agriculture concept provides a general framework which policy makers can use to effect change in different areas of the economy